THE IMPORTANCE OF SEMIOTICS IN THE PROCESS OF EDUCATIONAL DESIGN AND ANALYSIS OF SEMIOTIC SYSTEMS (Journal of Universal Science Research, 2023)
In this article, about the fields of semiotics and their limits, as well as their types, the importance of semiotic aspects, its application, the necessary pedagogical conditions, the scientists and their views, the branches, directions of semiotics and its use in our daily life. It is mentioned how we can use it.